Characterization on Thermal And Mechanical Properties of Non-Covalent Polyethyleneimine Wrapped on Graphene Nanoplatelets Within NR/EPDM Rubber Blend Nanocomposites - Razak, J.A.; Mohamad, N.; Ab Maulod, H.E.; Lau, K.T.; Munawar, R.F.; Abd Manaf, M.E.; Ismail, S.; Mahamood, M.A. (Journal of Advanced Manufacturing Technology (JAMT), 2017)
This study focused on the characterization of Natural Rubber (NR)/Ethylene Propylene Diene Monomer (EPDM) filled Graphene Nanoplatelets (GNPs) nanocomposites. The effects of GNPs non-covalent surface treatment using polyethyleneimine (PEI) and different loading of filler addition (0.25-5.00 wt. %) to cure characteristics, thermo-mechanical and thermal degradation properties of produced NR/EPDM rubber blends nanocomposites were analyzed and inter-correlated with their fracture morphologies. The surface treatment of GNPs was found to enhance the fillermatrices interaction in the NR/EPDM blend nanocomposites compared with unfilled and untreated GNPs filled NR/EPDM systems at similar loadings. The nanocomposites with 3.00 wt. % of PEI-treated GNPs possessed outstanding mechanical properties compared with unfilled NR/EPDM blends and filled nanocomposites without treatment (tensile strength of 27.78 MPa, 19.65 MPa and 23.34 MPa; respectively). The results were supported with thermal and dynamic analyses. Highly homogeneous dispersion of GNPs nanofillers and the presence of strong interfacial interaction between the matrix and reinforcement nanofiller resulted in an excellent thermal-mechanical properties of nanocomposites filled with 3.00 wt. % PEI treated GNPs. Obvious fractured morphological changes due to the noncovalent treatment provided hints on the role of GNPs treatment in improving the NR/EPDM blends mechanical and thermal properties.